Privacy at the margins - Skinner-Thompson, Scott, 1982- (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2021)
"Privacy often suffers in courts of law and as a legislative or regulatory priority. Privacy, in effect, is marginalized as a right and frequently ranked below security or law enforcement concerns. Often it is even ranked below administrative, personal, or corporate convenience. At the same time, privacy is of acute significance for members of marginalized communities-queer folk, racial and religious minorities, women, immigrants, people living with disabilities, people living in poverty, workers, and those at the intersections. Why is it that privacy receives limited protection from courts and legislatures notwithstanding the heightened necessity of privacy for communities fighting for lived equality; communities currently at the margins? What are the particular doctrinal limitations of privacy law that exacerbate the precariousness of marginalized communities? Are there nevertheless undercurrents within certain judicial contexts that, if emphasized, might lead to greater protection for those in precarious positions? Are there ways of thinking about privacy rights that might lead to more robust privacy protection by courts and lawmakers and better capture why privacy is of critical importance, particularly for vulnerable communities? Put differently, can privacy be transformed from a liberal, individualistic value into an anti-oppression legal tool?"--
No privacy in public = no privacy for the precarious -- Performative privacy in theory and practice -- Performative privacy's payoffs -- Containing corporate & privatized surveillance -- Outing privacy as anti-subordination -- Equal protection privacy.
Keywords: Privacy, Right of